Assessment of the Benefits of the ISO/IEC 42001 AI Management System: Insights from Selected Brazilian Logistics Experts: An Empirical Study - Alanna Oeiras da Costa Mazzinghy; Raurielly Maria dos Santos e Silva; Reimison Moreira Fernandes; Edney Dias Batista; Ailson Renan Santos Picanço; Nathália Jucá Monteiro; Daniel Meireles de Amorim; Brenda de Farias Oliveira Cardoso; Jonhatan Magno Norte da Silva; Vitor William Batista Martins (Standards)
(1) Background: This study aimed to analyze and rank the benefits of adopting Artificial Intelligence (AI) in the logistics area, considering the opinions of professionals working in the Brazilian logistics sector through the implementation of ISO/IEC 42001. (2) Methods: The procedures adopted included a literature review to identify the benefits of the use and the application of a survey aimed at professionals in the logistics sector. The analysis used the TOPSIS method to identify and rank the most decisive benefits. (3) Results: Of the 15 benefits mapped in the literature, the professionals attributed the greatest importance to customer satisfaction, operational efficiency, incentives for innovation, and improving the company’s image and competitive advantage. The results indicate that adopting ISO/IEC 42001 not only promotes process optimization and cost reduction, but also encourages innovation and strengthens competitiveness in the market. (4) Conclusions: The implementation of this standard is vital for companies in the logistics sector, especially in a Brazilian context of major infrastructural and regulatory challenges. The findings highlight the need for a strategic approach to the adoption of AI, emphasizing the importance of efficient logistics management and ethical practices in the application of this technology.